2016
DOI: 10.19104/jfnd.2015.101
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum Polysaccharides and Terpenoids: Profile and Health Benefits

Abstract: Recent studies have shown that mushrooms are recognized as a promising source of functional and nutraceutical compounds. The species Ganoderma lucidum (also called Reishi or Lingzhi) is a mushroom used in medicine because Chinese attributes to this fungus better health and longevity. Among the numerous bioactive compounds identified in G. lucidum are polysaccharides mostly β-glucans, heteropolysaccharides or glycoproteins, terpenoids mostly ganoderic acids and derivatives, as well as many other bioactive prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 71 publications
(59 reference statements)
0
10
0
1
Order By: Relevance
“…The HPLC-DAD-ESI/MS analyses of the fruiting bodies have revealed the presence of triterpenes such as ganoderiol F, ganoderic acid B, ganoderiol B, lucidenic acid O, lucidenic lactone and cerevisterol. [9][10][11] Because of their well-reported bioactive properties, some studies focused on the optimization of the cultivation practices of this mushroom have been conducted. Among them, the use of submerged fer-mentation by manipulating parameters such as the medium components, oxygen supply and pH aiming at achieving the biotechnological production of triterpenes was reported.…”
Section: Introductionmentioning
confidence: 99%
“…The HPLC-DAD-ESI/MS analyses of the fruiting bodies have revealed the presence of triterpenes such as ganoderiol F, ganoderic acid B, ganoderiol B, lucidenic acid O, lucidenic lactone and cerevisterol. [9][10][11] Because of their well-reported bioactive properties, some studies focused on the optimization of the cultivation practices of this mushroom have been conducted. Among them, the use of submerged fer-mentation by manipulating parameters such as the medium components, oxygen supply and pH aiming at achieving the biotechnological production of triterpenes was reported.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria and her neighboring West African states, mushroom are consumed for their nutritional benefit rather than for their medicinal values. The component parts of this mushroom including the mycelium, fruit bodies and spores have been demonstrated to exhibit different bioactive properties including antioxidant [15], antitumor [9], anti-inflammatory [10], antidiabetic [31], antimicrobial and antimalarial [12–14] activities, and they are currently being deployed in the management of diseases such as cancer hypertension), immunosuppression and hypercholesterolemia [32]. Based on the positive attributes of mushroom consumption on animal nutrition and health, increase awareness on the inclusion of mushroom in our daily meal is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidences revealed that the terpenoids are the most important biologically active substances in Ganoderma lucidum due to their varying pharmacological applications [8, 9]. Terpenoids extracted from Ganoderma lucidum have been demonstrated to exhibit anti-hypertensive [8], hypocholesterolemic [10, 11], hepatoprotective [12], and cytotoxicity against numerous cancer cell lines [13]. A recent study by Oluba et al [15] demonstrated the promising potential of crude chloroform extract of Ganoderma lucidum fruit body as an anti-plasmodial agent.…”
Section: Introductionmentioning
confidence: 99%
“…It is called white rot fungus because of its ability to degrade lignocellulosic materials such as wood [4]. The mushroom is popular due to its pharmaceutical importance rather than its nutritional benefits because of its hard texture and bitter taste [5].This group of mushrooms is an underutilize source of bioactive pharmaceutical compounds [6]. The mushroom is used in folk medicine to prevent, manage or cure many diseases such as hepatitis, gastric ulcer, hypertension, bronchitis and hypercholesterolemia [7].…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial activity of G. lucidum extract from basidiocarp against Gram-positive bacteria has also been reported [8]. Chinese believes that G. lucidum contributes to longevity and also serve as therapeutic factory [5]. DNA protection from breakage of strand triggered by UV irradiation or hydroxyl radicals is another protective role of G. lucidum [9].…”
Section: Introductionmentioning
confidence: 99%